ANALYSIS OF MUDHARABAH FINANCING AND MUSYARAKAH FINANCING OF ISLAMIC COMMERCIAL BANKS IN INDONESIA BEFORE AND DURING THE COVID-19 PANDEMIC - Sri Mulyati; Bambang Sugiharto; Syifa Ariella Putri; Annisa Putri Kartini (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2023)
This study aims to determine the development of mudharabah financing and musyarakah of Islamic commercial banks before and during the Covid-2019 pandemic and whether there are differences in mudharabah financing and musyarakah of Islamic commercial banks in Indonesia before and during the Covid-19 pandemic. This study used samples on Islamic commercial banks registered with the Financial Services Authority with conditions before (2018-2019 period) and during the Covid-19 pandemic (2020-2021 period). The data used in the study were secondary data with data collection techniques using online data tracing and analyzed using a quantitative descriptive method that compared data on mudharabah financing and islamic commercial bank musyarakah before and during the Covid-19 pandemic on annual financial statements and tested using a test tool, namely a paired sample t-test. The results of this study can be concluded that the development of mudharabah financing and musyarakah of Islamic commercial banks before and during the Covid-2019 pandemic experienced fluctuating developments. Then there is no significant difference between mudharabah and musyarakah financing of Islamic commercial banks in Indonesia before and during the covid-19 pandemic.